Kinase Suppressor of Ras 2 (KSR2) Regulates Tumor Cell Transformation via AMPK - Fernandez, Mario R. (American Society for Microbiology, 2012)
Kinase suppressor of Ras 1 (KSR1) and KSR2 are scaffolds that promote extracellular signal-regulated kinase (ERK) signaling but have dramatically different physiological functions. KSR2(−/−) mice show marked deficits in energy expenditure that cause obesity. In contrast, KSR1 disruption has inconsequential effects on development but dramatically suppresses tumor formation by activated Ras. We examined the role of KSR2 in the generation and maintenance of the transformed phenotype in KSR1(−/−) mouse embryo fibroblasts (MEFs) expressing activated Ras(V12) and in tumor cell lines MIN6 and NG108-15. KSR2 rescued ERK activation and accelerated proliferation in KSR1(−/−) MEFs. KSR2 expression alone induced anchorage-independent growth and synergized with the transforming effects of Ras(V12). Similarly, RNA interference (RNAi) of KSR2 in MIN6 and NG108-15 cells inhibited proliferation and colony formation, with concomitant defects in AMP-activated protein kinase (AMPK) signaling, nutrient metabolism, and metabolic capacity. While constitutive activation of AMPK was sufficient to complement the loss of KSR2 in metabolic signaling and anchorage-independent growth, KSR2 RNAi, MEK inhibition, and expression of a KSR2 mutant unable to interact with ERK demonstrated that mitogen-activated protein (MAP) kinase signaling is dispensable for the transformed phenotype of these cells. These data show that KSR2 is essential to tumor cell energy homeostasis and critical to the integration of mitogenic and metabolic signaling pathways.